2020
DOI: 10.1002/mrd.23391
|View full text |Cite
|
Sign up to set email alerts
|

Expression of chemerin and its receptors in the ovaries of prepubertal and mature gilts

Abstract: Recent studies have demonstrated that chemerin participates in the regulation of female reproductive function at the level of the ovaries. Due to the lack of data concerning the presence of the chemerin system (chemerin and its receptors: CMKLR1, GPR1, CCRL2) in the ovaries of pigs, one of the most economically important livestock species, the aim of this study was to investigate the expression and localization of chemerin and its receptors in the ovaries of prepubertal and mature gilts. We also aimed to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Large luteal cells form from granulosa cells after ovulation, while small luteal cells form from theca; our previous paper documented vaspin abundance in the granulosa and theca cells (Kurowska et al 2019a). Studies have demonstrated the luteal-phase-dependent expression of other adipokines like apelin (Różycka et al 2018), adiponectin (Maleszka et al 2014) or chemerin (Rytelewska et al 2020) in CL.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Large luteal cells form from granulosa cells after ovulation, while small luteal cells form from theca; our previous paper documented vaspin abundance in the granulosa and theca cells (Kurowska et al 2019a). Studies have demonstrated the luteal-phase-dependent expression of other adipokines like apelin (Różycka et al 2018), adiponectin (Maleszka et al 2014) or chemerin (Rytelewska et al 2020) in CL.…”
Section: Discussionmentioning
confidence: 90%
“…Sows were sacrificed during slaughter according to European Legislation (EFSA, AHAW/04-027). Ovaries were transported to the laboratory in PBS with an antibiotic-antimycotic solution within 30 min of collection, then CLs were isolated from the ovaries after morphological examination at the early (2-3 days after ovulation, the presence of corpora hemorrhagica), middle (10-12 days after ovulation, the phase when CL activity is the highest in the cycle), and late (14-16 days after ovulation, the phase of luteolysis) stages of the luteal phase (Rytelewska et al 2020). To determine vaspin/ GRP78 mRNA expression, CLs (n = 10 animal per stage, 1 CL from 1 animal, so the total number of animals was 30) were immediately frozen in liquid nitrogen and stored at −70°C.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Our recent studies have shown the presence of all three CHEM-associated receptors in selected structures of the pig hypothalamus [16] and ovary [17] during the estrous cycle and early pregnancy, which allowed us to conclude that CHEM has a direct effect on the hypothalamic-pituitary-gonadal regulatory axis (HPG) by modifying the functioning of its upstream structures. We hypothesized that CHEM may have endocrine effects on downstream structures of the HPG axis, in particular on CL producing steroid hormones, significantly modifying reproductive processes in mammals.…”
Section: Introductionmentioning
confidence: 91%
“…The expression of chemerin and its receptors in the porcine hypothalamic structures responsible for gonadoliberin (GnRH) production, as well as in the pituitary gonadotrophs suggests the potential involvement of the adipokine in the regulation of the reproductive functions [ 14 , 15 ]. Chemerin system expression was observed in the human uterus [ 18 , 19 ], in human and rat placenta [ 1 , 20 ], in the ovaries of women and rodents [ 1 , 21 , 22 ], and in porcine ovaries, uteri, trophoblasts, and conceptuses [ 23 , 24 ]. The expression of the chemerin system components in the endometrium, trophoblasts, placentas, and conceptuses suggests that the adipokine may play an important role in the foeto–maternal crosstalk during early pregnancy, as well as, through the placenta, across the whole gestation period.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research revealed changes in the expression of the chemerin system in porcine uterine and ovarian tissues and demonstrated changes in serum chemerin concentrations during the estrous cycle and early gestation. These findings suggest that chemerin system expression may be dependent on the hormonal milieu [ 14 , 23 , 24 ]. Similar observations were made by Yang et al, [ 26 ] who reported that chemerin and GPR1 expression in the ovaries of mice varied during the estrous cycle.…”
Section: Introductionmentioning
confidence: 99%